Ilmu Pengetahuan dalam Bingkai Konstruksi Sosial: Analisis Perspektif Berger dan Luckmann - Orin Maryati; Yusuf Tri Herlambang (Ideguru: Jurnal Karya Ilmiah Guru, 2025)
Science, in the conventional tradition, is often viewed as a body of objective truths grounded in observation and experimentation. However, the sociology of knowledge asserts that science does not emerge in a vacuum; rather, it is shaped by complex social processes. Social reality, including scientific knowledge, is constructed through interaction, institutionalization, and legitimation, such that scientific truth is fundamentally a socially recognized construction. This study aims to analyze science as a social construction from several perspectives, particularly concerning the processes of externalization, objectivation, and internalization in the formation of scientific reality. The method employed is a literature review derived from various online sources. A literature review may be understood as an explanation or description of scholarly works relevant to a particular topic. In this study, the literature consists of books, articles, journals, and other relevant references to support the analysis of the relationship between scientific knowledge and societal development. The findings indicate that the ideas of various scholars provide an essential foundation for understanding that science not only influences social life but is also shaped by the social factors within it. In other words, scientific knowledge cannot be separated from the social context that surrounds it. This reciprocal relationship demonstrates how society and science mutually construct one another, giving rise to diverse forms of reality across different spaces and times. Therefore, the application of scientific knowledge in society must always be understood within a broader social framework.